Educational Policy Analysis in Increasing Postgraduate Study Interest of Education Students: A Systematic Literature Review - Ella Febriyanti; Eddy Haryanto; Masbirorotni Masbirorotni (ITScience (Information Technology and Science), 2026)
This study is motivated by the relatively low interest among education students in pursuing postgraduate studies, despite their strategic role in improving the quality of human resources and supporting sustainable educational development. This study aims to analyze the factors influencing students’ interest in postgraduate study and to examine the role of education policy in strengthening such interest. The research employed a Systematic Literature Review (SLR) approach based on the PRISMA 2020 guidelines. Data were collected from 15 peer-reviewed articles published between 2020 and 2025 and analyzed using thematic analysis. The findings indicate that students’ interest in postgraduate study is influenced by three main factors: internal, external, and policy-related factors. Internal factors, including motivation, self-efficacy, academic aspirations, and career orientation, serve as the primary drivers of students’ intentions. External factors, such as economic conditions, social support, institutional environment, and access to information, may either facilitate or hinder students’ decisions. Meanwhile, education policies, including scholarship provision, program flexibility, affordable tuition, and the quality of academic services, play a significant role as enabling factors that improve access and participation in postgraduate education. These findings also highlight the importance of strengthening collaboration among universities, policymakers, and students to create sustainable postgraduate education opportunities. In conclusion, increasing students’ interest in pursuing postgraduate studies requires an integrated approach that combines individual motivation, supportive environments, and adaptive, inclusive, and student-centered education policies.